A model-based approach for inspection of aeronautical multi-layered structures by eddy currents. Issue 1 (30th October 2018) - Cung, Long Thanh; Nguyen, Nam Hoang; Joubert, Pierre Yves; Vourch, Eric; Larzabal, Pascal
Abstract : Purpose: The purpose of this paper is to propose an approach, which is easy to implement, for estimating the thickness of the air layer that may separate metallic parts in some aeronautical assemblies, by using the eddy current method. Design/methodology/approach: Based on an experimental study of the coupling of a magnetic cup core coil sensor with a metallic layered structure (consisting of first metal layer/air layer/second metal layer), which is confirmed by finite element modelling simulations, an inversion technique relying on a polynomial forward model of the coupling is proposed to estimate the air layer thickness. The least squares and the nonnegative least squares algorithms are applied and analysed to obtain the estimation results. Findings: The choice of an appropriate inversion technique to optimize the estimation results is dependent on the signal-to-noise ratio of measured data. The obtained estimation error is smaller than a few percent, for both simulated and experimental data. The proposed approach can be used to estimate both the air layer thickness and the second metal layer thickness simultaneously/separately. Originality/value: This model-based approach is easy to implement and available to all types of eddy current sensors.